Loss-Based Retributive Justifications of Punishment. (22nd May 2017) - Chau, Peter
Abstract: Retributive justifications of punishment that focus on the gain of offenders, like those offered by Herbert Morris and Jeffrie Murphy, have been subjected to sustained and persuasive criticism. Three authors (Daniel McDermott, Richard Lippke and Göran Duus-Otterström) have, in their fairly recent works, offered retributive justifications of punishment that focus instead on the loss suffered by victims. I will argue that these loss-based justifications, despite their ingenuity, suffer from serious defects.